Role of endoplasmic reticulum stress in lipopolysaccharide-inhibited mouse granulosa cell estradiol production - Lanjie LEI; Junbang GE; Hui ZHAO; Xiangguo WANG; Lei YANG (The Society for Reproduction and Development, 2019)
The decrease in the level of estradiol (E2) in granulosa cells caused by lipopolysaccharide (LPS) is one of the major causes of infertility underlying postpartum uterine infections; the precise molecular mechanism of which remains elusive. This study investigated the role of endoplasmic reticulum (ER) stress in LPS-induced E2 decrease in mouse granulosa cells. Our results showed that LPS increased the pro-inflammatory cytokines [(interleukin (IL)-1β, IL-6, IL-8, and tumor necrosis factor (TNF)-α)], activated ER stress marker protein expression [(glucose-regulated protein 78 (GRP78) and CCAAT/enhancer-binding protein homologous protein (CHOP)], and decreased cytochrome P450 family 19 subfamily A member 1 (Cyp19a1) expression and E2 production. Moreover, inhibition of ER stress by 4-phenylbutyrate (4-PBA) attenuated thapsigargin-(TG, ER stress agonist) or LPS-induced reduction of Cyp19a1 and E2, pro-inflammatory cytokines expression (IL-1β, IL-6, IL-8, and TNF-α), and the expression of CHOP and GRP78. Additionally, inhibition of toll-like receptor 4 (TLR4) by resatorvid (TAK-242) reversed the inhibitory effects of LPS on Cyp19a1 expression and E2 production, activation of GRP78 and CHOP, and expression of IL-1β, IL-6, IL-8, and TNF-α. In summary, our study suggests that ER stress is involved in LPS-inhibited E2 production in mouse granulosa cells.